Onde começa ou termina o território pátrio: os estrategistas da fronteira: empresários uruguaios, política e a indústria do charque no extremo oeste do Rio Grande do Sul (Quaraí 1893-1928) - Volkmer, Márcia Solange (Universidade do Vale do Rio do Sinos, 2007)
This study encompasses the social, political and economic insertion of a group of uruguayan industrialists in Rio Grande do Sul between 1893 – 1928. They formed a party of “saladeros” responsible for the refreshing of the productive structure and for the boost in the “charque” industrial activity in the farther west part of the state in the late XIX century. The research and text conceptual frameworks reveal the particular trajectory of these men, with the actions of the industrialist Emilio Calo forming the narrative link through the chapters. The role played by these industrialists and their industries and, particularly, those situated in Quaraí, shows up the existence of a business organization resulting from personal relationships and interests bonding. The cattle activity and it’s participation in the state’s economy, the “coronelistas” relationships of the border and the contacts with the Uruguay Republic are discussed. Along the chapters, the research points to the frontier strategical utilization by t
Keywords: charqueadas; economia; empresários uruguaios; fronteira; geopolítica; Rio Grande do Sul; Ciências Humanas